2008
DOI: 10.1111/j.1875-595x.2008.tb00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic correlates of early childhood caries prevalence and severity in a developing country - South Africa

Abstract: The study findings support the implementation of an integrated primary oral health care strategy in order to address the underlying socio-economic determinants of ECC in South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 27 publications
2
34
0
2
Order By: Relevance
“…Future caries-preventive approaches are needed for the primary dentition, especially in early childhood, as international studies report a high or even rising prevalence of early childhood caries [Jin et al, 2003;Postma et al, 2008;Treuner and Splieth, 2013]. Early childhood caries is clearly linked to socio-economic status and still persists after the caries decline.…”
Section: Exceptions and Pocketsmentioning
confidence: 99%
“…Future caries-preventive approaches are needed for the primary dentition, especially in early childhood, as international studies report a high or even rising prevalence of early childhood caries [Jin et al, 2003;Postma et al, 2008;Treuner and Splieth, 2013]. Early childhood caries is clearly linked to socio-economic status and still persists after the caries decline.…”
Section: Exceptions and Pocketsmentioning
confidence: 99%
“…Advanced forms of this disease, severe ECC, can destroy the primary dentition and is the major reason for hospital visits for young children (42). Severe ECC disproportionately affects disadvantaged ethnic and socioeconomic groups and can affect over 50% of the children in these groups (2,19,23,38,55).…”
mentioning
confidence: 99%
“…Some studies have considered the individual contribution of socioeconomic context or the development of dental caries in children [22,23]. These studies found that social status, low paternal education, and low family income provide worst oral health conditions [24,25,26,27,28,29]. On the other hand, other studies have demonstrated that these factors cannot be considered a determining factor [30].…”
Section: Discussionmentioning
confidence: 99%
“…Palavras-chave: Serviços de saúde; Epidemiologia; Cárie dentária 24 Rev Odonto Cienc 2017;32(1): [23][24][25][26][27] Dental caries in children assisted on a dental school clinic | De Sousa et al …”
Section: Introductionunclassified
See 1 more Smart Citation